Difficult Airway Intubation Due to Mouth Opening Limitation Caused by Mandibular Abscess: A Case Report - Wiliam Yuhono; Michael Jaya (Universitas Wijaya Kusuma Surabaya, 2023)
Appropriate management of difficult airway is imperative, particularly in cases with anticipated difficult airway. It customarily requires deliberate perioperative assessment. In this article we present a case of limited mouth opening along with restricted mobility of the temporomandibular joint secondary to mandibular abscess which requires surgical intervention. Preoperatively, difficult airway intubation was expected (based on LEMON mnemonic on preoperative evaluation). Therefore, Macintosh video laryngoscope and fiberoptic bronchoscope was prepared to aid in intubation. Due to the patient’s anxiety towards the procedure, the intubation was done while the patient is asleep. Preoxygenation was uneventfully. Following induction with general anesthesia, several attempts to conduct nasotracheal intubation using Macintosh video laryngoscope were made but all were abortive. This failed attempt is primarily due to the limited mouth opening and jaw mobility. Hence, fiberoptic bronchoscope-assisted nasotracheal intubation was conducted and was able to achieve airway patency. In conclusion, preoperative management holds great importance in selecting airway management strategy. To add, fiberoptic bronchoscope-assisted intubation is a safe option for intubation